Modified surgical concept for fulminant pulmonary embolism - Jakob, Heinz; Vahl, Christian-Friedrich; Lange, Rüdiger; Micek, Mario; Tanzeem, Ahmed; Hagl, Siegfried (European journal of cardio-thoracic surgery, 1995)
Surgical intervention in fulminant pulmonary embolism (PE) is stillassociated with an overall 30% fatal outcome which increases to about 60%when cardiopulmonary resuscitation (CPR) is necessary. Despite unfavorableconditions like hemodynamic instability, failed lysis or CPR, the surgicalstrategy might have a certain impact on the patient's outcome since 30-40%of the surgical mortality is related to persistent right heart failure andearly thromboembolic recurrence. From 1/88 to 8/94 a total of 25 patients(15 females, 10 men, mean age 57 [25-78]) years underwent emergencypulmonary embolectomy with the use of the heart-lung machine. Seventeenpatients were operated upon between 1988 and 1992. A standard approach bycentral pulmonary artery incision with extraction of adjacent pulmonaryemboli using forceps, suction of Fogarty catheters was used. Six of thesepatients (35%) died, with four out of six operated upon under CPR. Since1993 we have used a modified surgical strategy in eight patients. Fivepatients (63%) were operated on after or under CPR. In these cases, leftand right pulmonary arteries were incised peripherally and all segmentalarteries were desobliterated selectively using small suction devices.Thereafter the right atrium was opened and inspected. After removal of theinferior caval vein cannula all inferior body blood was taken withcardiotomy suction while both legs and the abdomen were massagedcentripetally to mobilize additional fresh thrombotic material. In threecases up to 50 cm long thrombi could be delivered. All patients havesurvived to date with two patients receiving a LGM caval filter placedpercutaneously after bilateral postoperative phlebography had revealedongoing thrombotic disease. We conclude that selective desobliteration ofevery segmental pulmonary artery in combination with simultaneous clearanceof major body veins from additional thrombotic material will probably lowersurgical mortality in these critically ill patients.
Gesehen am 16.06.2025